Efektivitas Pemanfaatan Laboratorium Biologi Terhadap Hasil Belajar Siswa di SMA Negeri 1 Tikke Raya - Rahmadani; Bialangi, Mursito; Buntu, Amalia; Laenggeng, Abd Hakim; Rauf, Abd; Astija (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to describe the effectiveness of the use of biology laboratories on student learning outcomes at SMA Negeri 1 Tikke Raya. This type of research uses a quantitative quasi-experimental design using a pretest and posttest control group design. Quantitative data are in the form of measurement results of student learning outcomes. The population in this study were all 145 students of class X of SMA Negeri 1 Tikke Raya. Sampling used a purposive sampling technique, and the sample in this study was 2 classes consisting of class X1 as the Experimental Class and X2 as the control class. Data collection techniques used observation and tests. The results showed that the use of biology laboratories proved to be more effective in improving the learning outcomes of class X students of SMA Negeri 1 Tikke Raya compared to conventional methods. The results of the analysis showed an increase in both groups, but the experimental group obtained significantly higher post-test scores, indicating that the use of laboratories had a positive effect on biology learning outcomes.